2014
DOI: 10.1061/(asce)em.1943-7889.0000747
|View full text |Cite
|
Sign up to set email alerts
|

High-Order Microplane Theory for Quasi-Brittle Materials with Multiple Characteristic Lengths

Abstract: The heterogeneous internal structure of quasi-brittle materials governs several aspects of their behavior, especially in the nonlinear range. Size and spacing of weak spots (e.g., aggregate-matrix interfaces, flaws, and slip planes) where failure is likely to occur are two of the most important material characteristic lengths that can be used to characterize the micro-and meso-structure of these materials. Discrete (lattice and particle) models can be conveniently used to directly model these geometrical featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

6
4

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 66 publications
1
38
0
Order By: Relevance
“…Also, in a straightforward manner without mathematical complexity, both frameworks are able to consider inherent and induced anisotropy well as a significant feature. Multi-plane models with different formulations have also been successfully developed for other materials such as polycrystalline metals, rock, soil, rigid foam and shape memory alloys, fiber-reinforced concrete and composite laminates and so on [27]. Some great advantages of multi-plane models were reviewed in Bazant et al [28] and Brocca and Bazant [29].…”
Section: Constitutive Equations For the Rate Dependent Multi-laminatementioning
confidence: 99%
“…Also, in a straightforward manner without mathematical complexity, both frameworks are able to consider inherent and induced anisotropy well as a significant feature. Multi-plane models with different formulations have also been successfully developed for other materials such as polycrystalline metals, rock, soil, rigid foam and shape memory alloys, fiber-reinforced concrete and composite laminates and so on [27]. Some great advantages of multi-plane models were reviewed in Bazant et al [28] and Brocca and Bazant [29].…”
Section: Constitutive Equations For the Rate Dependent Multi-laminatementioning
confidence: 99%
“…Concrete is often approximated as statistically homogenous at macroscopic scale, yet its macroscopic behaviour demonstrates strain softening, quasi-brittleness and size effect [18]. The appearance and evolution of cracking due to mechanical loading and environmental exposure can be as well partially attributed to material heterogeneity of concrete.…”
Section: Combined Phenomenamentioning
confidence: 99%
“…It was recently demonstrated that the strain definitions in Eq. 17 correspond to the projection into the local system of references of the strain tensor typical of continuum mechanics [84][85][86]. By assuming additivity of strains, one can write:˙…”
Section: Mechanical Behaviormentioning
confidence: 99%